Notes on Early Land Plants Today. 23. A new synonym in Anthoceros (Anthocerotaceae, Anthocerotophyta) - Cargill, D. Christine; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Stephani (1916) described two species of Anthoceros Linnaeus (1753: 1139) from Queensland, Australia, but the application of these names has been unclear. Herbarium collections at B, BM, HBG, L, MEL, PC, and W were searched in an attempt to find original material of these taxa. Two packets were found at G in the Stephani herbarium, one bearing the name Anthoceros fragilis (barcode G-61292) and the other lablled Anthoceros fertilis (barcode G-61293). Both annotations were in Stephani’s handwriting and the specimens match the descriptions in the protologue.